TANTANGAN DAN PELUANG PEMBELAJARAN TEMATIK DALAM KERANGKA KURIKULUM MERDEKA - Siregar, Khofifah Choirun Nisya; Asrial Habibi Harahap; Rama Nida Siregar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the opportunities and challenges of thematic learning within the framework of the Merdeka Curriculum at the elementary education level. The method used is a literature study with a descriptive qualitative approach through the review of journals, scientific articles, and relevant academic sources. The results of the study show that thematic learning has great opportunities because it is in line with the principles of the Merdeka Curriculum, which emphasizes flexibility, cross-disciplinary integration, contextual learning, and strengthening the Pancasila Student Profile. However, its implementation still faces challenges, such as limited teacher understanding, difficulties in mapping competencies, time constraints, lack of parental support, and low technological proficiency. Overall, the success of thematic learning implementation is highly dependent on teacher readiness, school support, and continuous training.